Alpine Fault‐Related Microstructures and Anisotropy of the Mantle Beneath the Southern Alps, New Zealand. Issue 11 (7th November 2022) - Shao, Yilun; Prior, David J.; Scott, James M.; Kidder, Steven B.; Negrini, Marianne
Abstract: Mantle xenoliths from the Southern Alps, New Zealand, provide insight into the origin of mantle seismic anisotropy related to the Australian‐Pacific plate boundary. Most xenoliths from within 100 km lateral distance of the Alpine Fault are coarse grained, but a small number are finer grained protomylonites. The protomylonites contain connected networks of fine grains with a different crystallographic preferred orientation (CPO) to coarse porphyroclasts in the same xenolith, suggesting that protomylonites and coarse‐grained samples record different deformation kinematics. The CPOs of fine grains in protomylonites have monoclinic symmetry, with the 2‐fold rotation axis normal to a plane that contains olivine [010] and orthopyroxene [100] maxima, suggesting that the protomylonite deformation involved significant simple shear. Some coarse‐grained samples contain unconnected lenses and layers of fine grains with the same CPO as the coarse grains. Microstructures suggest that these fine grains formed by subgrain rotation recrystallization and that protomylonites may represent an up‐strain progression of this microstructure, where the connectivity of fine grains has allowed them to localize shear and develop a new Alpine Fault CPO. The samples tell us about the state of the mantle at 25 Ma, in the early history of the plate boundary. If this suite of samples is representative of the mantle beneath the Alpine Fault in the present day, then we can interpret the complex seismic anisotropy patterns in the lithospheric mantle as representative of blocks containing variably rotated older CPOs juxtaposed by narrow shear zones associated with Alpine Fault deformation. Plain Language Summary: The Earth's mantle lies beneath the crust. Samples of the mantle are ripped‐up by volcanic processes and brought to the Earth's surface: these are known as xenoliths. Slow shearing in the mantle aligns the crystals that make up the xenoliths. Electron Backscatter Diffraction (EBSD) allows us to measure crystal alignments in the xenoliths, whilst seismic data can map the large‐scale patterns of crystal alignment in the current mantle. Seismic data show quite complex patterns in the mantle below the Southern Alps of New Zealand. We use EBSD measurements to help understand these seismic data patterns and their potential relationship to the Alpine Fault; the major structure between the Australian and Pacific plates. The xenoliths include fine crystal sizes that we infer, from the patterns of crystal alignment, to be sheared rocks related to the Alpine Fault. Most xenoliths have much coarser crystals and we suggest that the crystal alignments pre‐date the Alpine Fault. The xenoliths were extracted from the mantle about 25 million years ago, in the earliest stages of the fault. We apply the inferences from the xenoliths to the seismic data patterns in the current mantle and suggest that Alpine Fault deformation in the mantle is limited to very narrow zones. Areas between these zones relate to deformation events that pre‐date the Alpine Fault. Key Points: Protomylonites cross‐cut coarse‐grained peridotite with different deformation kinematics in mantle xenoliths near the Alpine Fault Protomylonites represent localized shear in the lithospheric mantle associated with the early stages of the Alpine Fault (∼25 Ma) motion Seismic anisotropy in the lithosphere probably relates to mantle deformation that predates the Alpine Fault, but has been re‐oriented